PENEGAKAN HUKUM TERHADAP PELANGGARAN HAK EKSKLUSIF PENCIPTA FILM PADA PENYEDIA LAYANAN SITUS STREAMING DI INTERNET - Ridianita, Cyntia; Susanti, Erna; Triyana, Lily (Jurnal Ilmiah Advokasi, 2025)
Streaming Service Provider is a method of sending files in the form of video or audio that can be widely enjoyed by the public via the internet network from one computer to another and can be downloaded freely without any time limits. The purpose of this study is to be a reference for law enforcement in implementing fair, certain, and beneficial rules. The problem in this thesis is in the actions of perpetrators of violations of exclusive copyright of copyright who upload or distribute films. The results of this study found that the act of uploading films on one of the nobar24 streaming sites has fulfilled the elements of committing an act of violating the exclusive rights of the creator because the film is a cinematographic work protected in Article 40 letter m of the Copyright Law Number 28 of 2014. As for legal efforts that can be taken by the creator or copyright holder if there is a problem or dispute regarding copyright, dispute resolution can be done through non-court channels, in the form of alternative dispute resolution, arbitration or through the courts.Keywords: Exclusive Rights; Film; Website